SCHOOL MARKETING STRATEGIES IN INCREASING STUDENTS' INTEREST IN MADRASAH IBTIDAIYAH MUHAMMADIYAH PROGRAM KHUSUS - ADILA, DINDA YUNI; HIDAYATI, HANIFA NUR; HASANAH, RAHMATUL; PANGESTI, YUSYI'AFAH; ERNAWATI, FETTY (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
Marketing strategies are very important for every educational institution to understand. Cooperation and good relations with the community are very important in the marketing process. Educational institutions must have special strategies in marketing their educational services to attract public interest. Sometimes there are still many educational institutions that pay less attention to their marketing strategies. The purpose of this research is to describe the marketing strategy in Madrasah Ibtidaiyah Muhammadiyah Program Khusus Kartasura. The type of this research is qualitative, where the data collected is in the form of words not numbers. The data collection technique used interviews, observation, and documentation. Based on the research there is a marketing strategy in Madrasah Ibtidaiyah Muhammadiyah Program Khusus Kartasura in marketing through elements of the marketing mix which includes product, price, place, and promotion. ABSTRAK Strategi pemasaran sangat penting untuk dipahami oleh setiap lembaga pendidikan. Kerja sama dan hubungan baik dengan masyarakat sangat penting dalam proses pemasaran. Lembaga pendidikan harus mempunyai strategi khusus dalam memasarkan jasa pendidikannya untuk menarik minat masyarakat. Terkadang masih banyak lembaga pendidikan yang kurang memperhatikan strategi pemasarannya. Tujuan penelitian ini adalah untuk mendeskripsikan strategi pemasaran pada Madrasah Ibtidaiyah Program Khusus Muhammadiyah Kartasura. Jenis penelitian ini adalah kualitatif, dimana data yang dikumpulkan berupa kata-kata bukan angka. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Berdasarkan penelitian terdapat strategi pemasaran di Madrasah Ibtidaiyah Muhammadiyah Program Khusus Kartasura dalam pemasaran melalui unsur bauran pemasaran yang meliputi produk, harga, tempat, dan promosi.